Writing, Dreaming, and Freedom: Rokeya Hossain at the Limit of Reform in colonial Bangladesh - Parna Sengupta (Genre & Histoire)
This article looks at the work of Rokeya Sakhawat Hossain (1880-1932), the writer of Sultana’s Dream and an individual who is claimed as both a national figure in Bangladesh and a global figure by international feminists. I foreground Rokeya’s narrative and stylistic choices (the ‘how’ of her texts rather than the ‘what’) to reveal the ways in which her reflections on writing become a space in which she asserts women’s claims to authority and tries to capture the elusive nature of imagination and creativity. Drawing on the work of Hélène Cixous, I look at Rokeya’s experimentations with genre through her use of the waking dream, a narrative frame which allows her to draw attention to the act of composition as related to forms of inspiration and states of consciousness that are not reducible to a discourse of rationality or reform. The essay then suggests that another entry point to understand the waking dream is its place within the Islamic tradition, where dreams are often the vehicles through which the pious receive revelation, guidance and knowledge.